1983
DOI: 10.2307/1422208
|View full text |Cite
|
Sign up to set email alerts
|

Oddity and Dimension-Abstracted Oddity (DAO) in Squirrel Monkeys

Abstract: Four squirrel monkeys were trained on 10 pretraining oddity problems and a series of 6 conceptual oddity and dimension-abstracted oddity (DAO) tasks. These six tasks were presumed on logical grounds to comprise six levels of difficulty and were administered in the presumed order of difficulty. All tasks were performed significantly better than chance, but performances on tasks 1, 2, and 4 were better than those on tasks 3, 5, and 6. Discussion considered the kinds of evidence that are necessary for demonstrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 24 publications
(25 reference statements)
0
36
0
Order By: Relevance
“…Whether the study by Langworthy and Jennings demonstrated conceptual responding to oddity by rats depends on whether nonconcep~al odor cues were used to locate the reinforcers (see the 10-troduction to Experiment 2). Even so, these two studies involve easier tests of the oddity concept than some that have been performed successfully by primates (see Thomas & Frost, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether the study by Langworthy and Jennings demonstrated conceptual responding to oddity by rats depends on whether nonconcep~al odor cues were used to locate the reinforcers (see the 10-troduction to Experiment 2). Even so, these two studies involve easier tests of the oddity concept than some that have been performed successfully by primates (see Thomas & Frost, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Among tasks used with nonhumananimals, relative balance appears to have been addressed most clearly in "dimensionabstracted oddity" (DAO) tasks in which the nonodd stimuliare not identical, but do share more propertieswith each other than with the odd stimulus (e.g., Bernstein, 1961;Strong, Drash, & Hedges, 1968;Thomas & Frost, 1983), and in the more abstract versions of samenessdifference tasks (Premack, 1983;Smith, King, Witt, & Rickel, 1975). Although primates perform successfully on such tasks, apparently no attempts have been made to use DAO or the more abstract sameness-difference tasks with nonprimate animals.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The suggestion that learning might be slowed by reducing the number of stimulus attributes is supported by the Thomas and Frost (1983) finding that squirrel monkeys learn oddity discriminations more rapidly with two relevant stimulus dimensions compared to one stimulus dimension. Similarly, both old and young dogs perform well on object discrimination tasks in which the discriminanda differ in a number of perceptual attributes including color, shape, size, and form (Head et al 1998).…”
Section: Size Learningmentioning
confidence: 98%
“…Except for studies using nonhuman primates and one study using pigeons, claims for the use of the oddity concept by other nonhuman animals do not withstand close scrutiny (Thomas & Frost 1983). The issue is whether it was possible that the animal learned associations between the specific odd stimuli and reward or rather responded to oddity conceptually.…”
Section: Overcoming Contextual Variables Negative Results and Macphmentioning
confidence: 99%